Capacitação de alunos de escolas públicas para desenvolvimento de aplicativos para IOS - Santos, Gabriel Felipe Batista dos (2023)
There are many programming courses on the market for young people. However, most courses are basic, using software that is not used in the job market and with minimal contente does not prepare the student to work in the market. The objective of this work is to investigate how the maker culture combined with the Xcode development platform can facilitate the teaching-learning processo f programming and prepare students for the job market. As a case study to apply the maker culture in programming teaching, we created a programming course with an active methodology, where in each class the students were proposed the challenge of developing an application with the newly acquired knowledge. Forty first-year high school students from three public schools participated in this course. Then, all students attended a total of 20 classes, in addition to overtime to develop the proposed projects. In the end, 35 students completed the course and developed 19 applications, 12 of which are on the Apple Store, which shows the viability of the proposal.